2017
DOI: 10.14738/abr.511.3696
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Status and Life Expectancy in Lebanon: An Empirical Analysis

Abstract: This study has investigated the impact of socio-economic status on life expectancy in the case of Lebanon over the period of 1971 to 2014. Availability of food, CO2 emissions, secondary school enrollment, per capita income and population growth are used for reviewing socio-economic status of Lebanon. Johansen test is used for examining co-integration among variables. The results of Johansen co-integration show that there is co-integration among the variables of the model. The long run results of the model show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…In empirical studies, many researchers (Ali & Ahmad, 2014; Avcı & Çalişkan, 2023; Azam et al, 2023; Corman et al, 2018; Fayissa & Gutema, 2005; Rayhan et al, 2019), used life expectancy as an indicator of health output. Life expectancy is the most commonly used measure of health status in empirical studies aimed at estimating health production function.…”
Section: Theory Data and Methodologymentioning
confidence: 99%
“…In empirical studies, many researchers (Ali & Ahmad, 2014; Avcı & Çalişkan, 2023; Azam et al, 2023; Corman et al, 2018; Fayissa & Gutema, 2005; Rayhan et al, 2019), used life expectancy as an indicator of health output. Life expectancy is the most commonly used measure of health status in empirical studies aimed at estimating health production function.…”
Section: Theory Data and Methodologymentioning
confidence: 99%
“…The results showed that living in the city enhances the risk of getting sick and decreases physical activity. Ali and Audi (2019) examined the impact of urbanization on life expectancy in MENA countries from 2001 to 2016 by using Panel ARDL method. The results showed that urbanization has a positive and significant impact on life expectancy.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Among the control variables, per capita income and public sector expenditures on health are positively related with life expectancy, while fertility rate exerts a negative effect on life expectancy. Audi and Ali (2016) identify that socioeconomic factors have a strong influence on life expectancy, higher per capita income increases household's purchasing power and it gives a rise to health status in the long run. Availability of food is essential for human life, and higher income ensures its availability.…”
Section: Foreign Capital Flows and Life Expectancy: Role Of Instituti...mentioning
confidence: 99%